Adolescent identity formation through the role of the family in Wendelin Van Draanen's Flipped - Vira Mileniar Aqsa; Adeline Grace Marianne Litaay (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines how family environments influence adolescent identity formation as portrayed in Wendelin Van Draanen's novel Flipped (2001). The research focuses on the two central characters, Bryce Loski and Juli Baker, whose contrasting upbringings produce fundamentally different psychological trajectories across the course of the narrative. The study is guided by three research questions: how family environments influence the formation of the characters' personalities and values, what the novel reveals about the psychological impact of family on identity formation during adolescence, and how family dynamics contribute to the characters' emotional maturity and their changing perceptions of one another. This research applies a qualitative descriptive design using a psychological approach to literary analysis. The primary data source is Van Draanen's novel Flipped (2001), and the analysis draws on Erik Erikson's Theory of Psychosocial Development (1968) and James Marcia's Identity Status Model (1966) as its main analytical frameworks. Textual evidence including narrative descriptions, dialogue, and internal monologue is gathered and analyzed through close reading. The findings demonstrate that family environment is not simply one influence among many in adolescent development but the foundational condition that shapes what kind of identity formation becomes possible. Juli Baker's household, characterized by emotional honesty, parental modeling of genuine values, and open communication, produces an adolescent who develops a strong and self-directed sense of identity. Bryce Loski's household, characterized by social performance, conditional approval, and the reduction of human worth to material appearances, produces an adolescent operating in Identity Foreclosure who must work against his inherited identity before genuine development becomes possible. The study also reveals that the corrective influence of a single significant relational figure, in this case Bryce's grandfather Chet Duncan, is sufficient to open the possibility of genuine identity exploration even within a limiting family environment. The novel's dual narrative structure is itself a literary enactment of the study's central argument: that how an adolescent perceives and narrates the world is a direct product of the family environment that has shaped their developing sense of self.